The Effect of Work Safety Climate and Safety Knowledge on Safety Behavior in Production Employees of PT. Sumber Abadi Bersama - Bemby Andrian Rahmadhan; Titiek Ambarwati; Siti Nurhasanah (Universitas Muhammadiyah Malang, 2021)
The purpose of this study is to determine safety behavior, safety climate and knowledge of safety, the effect of work safety climate on employee safety behavior, safety knowledge on employee safety behavior, the effect of work safety climate and safety knowledge on safety behavior, and which of these variables have the most influence on behavior. This type of research is explanatory research and data collection using questionnaires. The population in this study were all employees in the production section at PT. Sumber Abadi Bersama with a sample size of 40 employees. The results of the analysis show that work safety behavior is in a good category. Safety behavior and safety climate have a significant effect on employee safety behavior.